Improving Mental Health Care in Developing Countries Through Digital Technologies: A Mini Narrative Review of the Chilean Case - Rojas, Graciela; Martínez, Vania; Martínez, Pablo; Franco, Pamela; Jiménez-Molina, Álvaro (Frontiers in Public Health, 2019)
The uneven distribution of mental health resources contributes to the burden of mental disorders in vulnerable groups, especially in developing countries. Internet-based interventions and digital technologies can contribute to reducing the gap between high prevalence of mental disorders, demand for treatment, and access to mental health care, thereby reducing inequities in mental health. This mini review summarizes the current state of the field of e-mental health research in Chile, showing its progress, limitations, and challenges. Internet-based interventions are at an early stage of development in Chile. The interventions included are heterogeneous in terms of participants (e.g., secondary students, patients, healthcare professionals) and contexts (e.g., rural, urban, schools, primary health care), aims, and modalities (e.g., website, online games). While these studies confirmed the feasibility of Internet-based interventions, the shortage of studies on effectiveness and cost-effectiveness makes it difficult to disseminate and scale up these Internet-based programs. However, the growing amount of knowledge accumulated in the Chilean context could guide practices in other developing countries for supporting the mental health of underserved populations.